The role of project management principles for controlling civil works contracts - Campero Q., Mario (Revista Ingeniería de Construcción, 2013)
The great amount of complaints that surge from construction contracts is a source of concern for both owners and contractors. This paper analyzes the causes that literature assigns to these complaints and concludes that they come fundamentally from the variety of issues that affect the execution of every project because of its character as a unique product or service and unexpected events that occur due to external factors. It concludes that an adequate way of managing this uncertainty and prevent these complaints is to fix contractual bases including the flexibility needed to accept changes with the appropriate economic compensations and to apply procedures that stabilize the work conditions so that the programming of activities is trustworthy. Finally, it incorporates a basic description of the recommended normalized team working between owner and contractor in order to prevent and resolve in time the effects of uncertainty that could give origin to conflicts.